TFPR: dispersion and cyclicality - Cooper, R; Ozturk, O (University of Oxford, 2024)
This paper studies the determinants of the dispersion and cyclicality of TFPR, a revenue based measure of total factor productivity. Recent business cycle models are built upon the assumption of countercyclical dispersion in TFPQ, a quantity based measure of total factor productivity, based on evidence of countercyclical dispersion in TFPR. But, these are very different measures of productivity. The distribution of TFPR is endogenous, dependent upon exogenous shocks and the endogenous determination of prices. An overlapping generations model with monopolistic competition and state dependent pricing is constructed to study the factors that shape the TFPR distribution. The focus is on three key data patterns: (i) countercyclical dispersion of TFPR, (ii) countercyclical dispersion of price changes and (iii) countercyclical frequency of price adjustment. The analysis uncovers two interesting scenarios in which these moments are matched. One arises in the presence of shocks to the dispersion of TFPQ along with a negatively correlated change in the mean of TFPQ. The second arises if the monetary authority responds to shocks to the dispersion of TFPQ by “leaning against the wind”. The findings are robust to the introduction of non-CES household preferences. Due to state contingent pricing, the model is nonlinear. Simple correlations mask these nonlinearities of the underlying economy.